Gestational weight gain and increased risk of cesarean delivery across body mass index categoriesAJOG Global Reports at a Glance - Pearl A. McElfish, PhD; Britni L. Ayers, PhD; Nicola L. Hawley, PhD; Aaron Caldwell, PhD; Austin Porter, DrPh; Michael D. Macechko, MD; Donya Watson, MD; Jennifer A. Callaghan-Koru, PhD; James P. Selig, PhD; Jennifer A. Andersen, PhD; Nirvana Manning, MD; Lanita White, PharmD; et al. (AJOG Global Reports)
BACKGROUND: Unnecessary cesarean delivery can have negative implications for both mothers and infants. In the United States, the proportion of women undergoing cesarean delivery exceeds the acceptable World Health Organization proportion. Reducing cesarean deliveries is a national goal of Centers for Disease Control and Prevention Healthy People 2030, the American College of Obstetricians and Gynecologists, and the Alliance for Innovation on Maternal Health. OBJECTIVE: This study aimed to examine if excessive gestational weight gain is associated with increased risk of cesarean delivery across multiple body mass index categories. STUDY DESIGN: Analysis was conducted using vital records data from the National Center for Health Statistics birth records. Only low-risk births were included (singleton, term-gestation [≥37 weeks], cephalic presentation, and first birth to exclude women who had a prior cesarean delivery). We used the rate of gestational weight gain (lb/wk) measured as both a categorical and continuous variable. These results were confirmed by a sensitivity analysis using total gestational weight gain (lb). RESULTS: Regardless of prepregnancy body mass index category, women with excessive gestational weight gain had a higher risk of cesarean delivery. Among women with a healthy prepregnancy body mass index, the risk of cesarean delivery decreased with appropriate weight gain, suggesting a potential protective effect of moderate weight gain for individuals with a healthy prepregnancy body mass index. However, weight gain beyond the appropriate level increased the risk of cesarean delivery. For women with overweight or obese prepregnancy body mass index, any increase in gestational weight gain was associated with a higher cesarean delivery risk. CONCLUSION: This study found a strong association between an excessive rate of gestational weight gain and the risk of cesarean delivery, regardless of prepregnancy body mass index, suggesting the need for continued efforts to reduce excessive gestational weight gain across populations.